The Effect of Scientific-Based Practicum Methods on Environmental Pollution Materials on Students' Science Process Skills - Shindi, Shindi; Suryanda, Ade; Sigit, Diana Vivanti (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2024)
This study aims to determine the influence of scientific-based practicum methods on environmental pollution materials on students' science process skills. This research employed a quantitative method with a quasi-experimental research design. This research was carried out from January to June 2024. The sampling technique employed was simple random sampling, obtaining 60 students divided into experimental and control classes. From the results of the pretest, the initial science process skills of students in both classes were high. Furthermore, the posttest results showed that there was an increase in science process skills, which was very high. The results of the independent sample t-test on the gain score data showed that the scientific-based practicum method on environmental pollution materials affected the students' science process skills. Based on the value of n gain in the experimental class, the effect is categorized as moderate. Thus, the practicum method with a scientific approach to environmental pollution materials can be used as an alternative solution to overcome the low skills of students' science processes.ABSTRAK: Penelitian ini bertujuan untuk mengetahui pengaruh metode praktikum berbasis saintifik pada materi pencemaran lingkungan terhadap keterampilan proses sains peserta didik. Penelitian ini berjenis kuantitatif dengan metode penelitian kuasi eksperimen. Penelitian ini dilaksanakan pada Januari – Juni 2024. Pengambilan sampel secara simple random sampling memperoleh 60 peserta didik yang terbagi dalam kelas eksperimen dan kelas kontrol. Dari hasil pretest, keterampilan proses sains awal peserta didik di kedua kelas termasuk tinggi, lalu hasil posttest menunjukkan adanya peningkatan keterampilan proses sains menjadi sangat tinggi. Hasil uji t-independen pada data gain score menunjukkan bahwa metode praktikum berbasis saintifik pada materi pencemaran lingkungan berpengaruh terhadap keterampilan proses sains peserta didik. Berdasarkan nilai n gain pada kelas eksperimen, pengaruh tersebut berkategori sedang. Dengan demikian, metode praktikum dengan pendekatan saintifik pada materi pencemaran lingkungan dapat dijadikan sebagai solusi alternatif untuk mengatasi rendahnya keterampilan proses sains peserta didik.